HP-1γ Controls High-Affinity Antibody Response to T-Dependent Antigens - Ha, Ngoc; Pham, Duc-Hung; Shahsafaei, Aliakbar; Naruse, Chie; Asano, Masahide; Thai, To-Ha (Frontiers in Immunology, 2014)
In vitro observations suggest a role for the mouse heterochromatin protein 1 γ (HP-1γ) in the immune system. However, it has not been shown if and how HP-1γ contributes to immunity in vivo. Here we show that in mice, HP-1γ positively regulates the germinal center reaction and high-affinity antibody response to thymus (T)-dependent antigens by limiting the size of CD8+ regulatory T-cell (Treg) compartment without affecting progenitor B- or T-cell development. Moreover, HP-1γ does not control cell proliferation or class switch recombination. Haploinsufficiency of cbx-3 (gene encoding HP-1γ) is sufficient to expand the CD8+ Treg population and impair the immune response in mice despite the presence of wild type HP-1α and HP-1β. This is the first in vivo evidence demonstrating the non-redundant role of HP-1γ in immunity.